Looking at the Crystal Ball - Rizzo, Toni (MD Conference Express, 2015)
Reductions in cardiovascular mortality have been achieved via improved prevention, diagnosis, and treatment. However, costs have risen accordingly. A future emphasis on health promotion and disease prevention through research, education, and mitigation of disease-causing environmental factors holds the promise of improving outcomes and reducing the cost of treating CV disease.